Investigating the effectiveness of innovative intervention based on compassion, awareness, resilience, and empowerment on burnout in nurses of two educational hospitals in Isfahan - Alireza Safaeian; Negah Tavakolifard; Azita Roohi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Burnout is a syndrome of emotional exhaustion, depersonalization, and low professional efficacy that health workers, especially nurses, experience the highest rates of this. Burnout causes stress and negative attitude towards work and feeling unable to perform tasks in the person. The purpose of this study was to investigate the effect of a method called compassion, awareness, resilience, and empowerment (CARE) on nurses' burnout. MATERIALS AND METHODS: This study was a semi-experimental study with control group, the statistical population in this study was nurses of Kashani Hospital in Isfahan as intervention group and nurses of Al-Zahra Hospital as control group. The samples were selected by stratified sampling. For both groups before and after and 3 months after the intervention, the burnout questionnaire (Maslach Burnout Inventory) was completed. The intervention was performed in 5 sessions of 90 min 1 day a week. Data were analyzed by SPSS version 25 software (IBM Inc., USA) and independent t-test, repeated measures analysis of variance and Chi-square test and Friedman test, significance level was set at P < 0.05. RESULTS: The comparison of mean and intensity of burnout and two dimensions of emotional exhaustion and depersonalization showed a difference between the two groups and this difference was statistically significant (P < 0.05). Mean of Individual performance also had a statistically significant difference between the two groups (P < 0.05), but its intensity did not change. CONCLUSION: CARE method can be effective in burnout of nurses and it can be used as a practical method. This training program can be implemented both preservice and in-service for health workers.